The second complete mitogenome of Scolopsis ciliata (Perciformes, Nemipteridae) to analyze control region structure and intraspecific variation. Issue 2 (3rd July 2019) - Wu, Ren-Xie; Miao, Ben-Ben; Niu, Su-Fang; Zhai, Yun; Zhang, Hao-Ran; Liu, Fang; Ou, Chun-Xiao
Abstract: In this study, we reported the complete mitogenome of Scolopsis ciliata sampled from the Beibu Gulf, South China Sea. It was 16, 734 bp in length and contained 37 canonical mitochondrial genes and 2 non-coding regions. Fifty-one single nucleotide polymorphisms and five insertion and deletions were detected between two S. ciliata mitogenomes, suggesting a high level of intraspecific genetic variation in the species. The control region contained termination associated sequence domain (TAS), central conserved domain (CSB-F, CSB-E, CSB-D, CSB-C, and CSB-A), and conserved sequence block domain (CSB-1, CSB-2, and CSB-3). The phylogenetic analysis of 21 complete mitogenome sequences well supports the phylogenetic position of S. ciliata and reveals the phylogenetic relationship of the genus Scolopsis .